2010
DOI: 10.1007/s11251-010-9156-z
|View full text |Cite
|
Sign up to set email alerts
|

Learning to design collaboratively: Participation of student designers in a Community of Innovation

Abstract: Creativity researchers have drawn on cognitive principles to characterize individual innovation. However, few comprehensive frameworks have been developed to relate social innovation to social cognition research. This article introduces the Communities of Innovation (COI) framework and examines its applications in a culture designed to promote collaborative creativity. Findings included evidence for some aspects of the COI model (flow and hacker ethic, entrepreneurship, collaboration and mentoring, sense of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Key to the success of the CFA were the weekly meetings where students questioned each other's progress, as well as the design decisions of their student directors and producers, in an atmosphere of safe critique and feedback. Previous research has found that critique and evaluative questioning, in an atmosphere of psychological safety (Rogers, 1954) can not only improve the learning of the one being critiqued, but also the one giving the critique (West & Hannafin, 2011). Developing this culture of safety and questioning is difficult, but can be accomplished with informal socializing (in the CFA, they often had pizza or other social events), and an environment where failure is not destructive to the individual, but rather a challenge that the group must overcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Key to the success of the CFA were the weekly meetings where students questioned each other's progress, as well as the design decisions of their student directors and producers, in an atmosphere of safe critique and feedback. Previous research has found that critique and evaluative questioning, in an atmosphere of psychological safety (Rogers, 1954) can not only improve the learning of the one being critiqued, but also the one giving the critique (West & Hannafin, 2011). Developing this culture of safety and questioning is difficult, but can be accomplished with informal socializing (in the CFA, they often had pizza or other social events), and an environment where failure is not destructive to the individual, but rather a challenge that the group must overcome.…”
Section: Discussionmentioning
confidence: 99%
“…One area of PBL that has received less attention in the research is how to teach problem-based learners to evaluate their progress and learn from their previous efforts. This is peculiar, since selfreflection and group evaluation are key components of effective group problem solving (Bielaczyc & Collins, 2006;Engeström, 1999;Hakkarainen, Palonen, Paavola, & Lehtinen, 2004;Sawyer, 2008) and community-based innovation (West & Hannafin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this was to help students "understand that design is an iterative process where tentative design decisions are made and then revised when additional information becomes available" (p. 24). Interestingly, West and Hannafi n ( 2011 ) found that students not only learned from the critiques they received on their designs but also through the process of critiquing the designs of others. Thus, the goal in most studio-oriented approaches is not only to provide students with opportunities to collaborate on a project but to give and receive feedback to improve their processes.…”
Section: Studio-based Pedagogy In Instructional Designmentioning
confidence: 99%
“…Existing research acknowledged that design processes are nonlinear and iterative and consist of a basic shell that includes a variation of the following foundations of inquiry: define, research, ideate, prototype, choose, implement, learn, and reflect (Findeli, 2001;Lawson, 1990;Sawyer & DeZutter, 2009;West & Hannafin, 2011). These foundations of inquiry can be woven into student-centered learning processes, such as DBL, which is a form of project-based learning (PBL) 2 .…”
Section: Key Findingsmentioning
confidence: 99%